Ecommerce Design Based Multi Vendor Case Study PT. Mutiara Katalog Indonesia: Ecommerce Design Based Multi Vendor Case Study PT. Mutiara Katalog Indonesia - Prasojo Herdy Sutanto (Jurnal Mantik, 2020)
In the beginning, PT. Mutiara Katalog Indonesia. In selling goods is still the traditional way. To achieve sales targets to consumers is still very difficult, recording sales data is also still using manual methods that use paper and books. Traditional data collection errors often occur so that this results in losses for the company. At present Ecommerce as a medium that can provide convenience for traders, in addition to wider product distribution and to achieve a more targeted sales approach. For Ecommerce transactions can be done with electronic media in an automatic way. With a descriptive method that applies data retrieval by interviewing also seeing firsthand the conditions in the field and study of literature, a problem is found to develop and find possible solutions, namely, how to improve operational performance and expand market share for this store. Application of eCommerce technology as a more effective and efficient way. This can also save data processing time and tend to be more accurate and faster in making reports to the owner. The preparation of the application includes the development stages which include requirements analysis, making data flow diagrams with UML Modeling as well as WEB-based programming languages ??namely PHP, Ajax, Jquery, JSon and MySqli. For testing the system using the Black Box and Alpha methods.